Perpaduan Teknik Modelling dengan Doa Sapu Jagat dalam Konseling Kelompok Behavioral untuk Pemantapan Pengambilan Keputusan Karier: Efektif atau Tidak? - Ramadhani, Deva; Prabawa, Abi Faizzarahman (JURNAL BIMBINGAN KONSELING FLOBAMORA, 2024)
This study aimed to test the effectiveness of behavioral group counseling by combining modeling techniques with sap jagat prayer to improve the stabilization of career decision-making in students. The research method used a quantitative pre-experimental design with one group pretest and post-test design. The participants in the study amounted to 8 students of SMAN 1 Bringin, Semarang Regency, who were taken using a purposive sampling technique. The criteria for sampling in this study are 1) Muslim students; 2) students who are still hesitant in making decisions, and 3) students who have a low level of career stabilization. The instrument used is the career decision-making stabilization scale developed from Jones's (1980) theory. The instrument consists of 31 items with a reliability value of 0.780. Data analysis techniques using t-test. The results showed p = 0.000 (p < 0.05), meaning that behavioral group counseling combined with modeling techniques with sapu jagat prayer effectively stabilizes career decision-making in students. This study has limitations on Muslim subjects, so a more comprehensive, varied subject free from religious bias is required to generalize the research results.